2016
DOI: 10.1097/aln.0000000000001108
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Validity of Three Methods for Measuring Postoperative Complications

Abstract: Background Anesthesiologists need tools to accurately track postoperative outcomes. The accuracy of patient report in identifying a wide variety of postoperative complications after diverse surgical procedures has not previously been investigated. Methods In this cohort study, 1,578 adult surgical patients completed a survey at least 30 days after their procedure asking if they had experienced any of 18 complications while in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
(26 reference statements)
2
10
0
1
Order By: Relevance
“…The validity of the outcomes determined by automated health record review has previously been compared with manual record review and patientreported outcomes. 36 Similar to another report, 37 this previous study 36 found large positive likelihood ratios with moderate sensitivity. Another study 38 Funding/Support: The study was supported by the Big Ideas Program, a BJC HealthCare and Washington University School of Medicine internal grant program hosted by the Healthcare Innovation Lab and the Institute for Informatics (Dr Abraham).…”
Section: Limitationssupporting
confidence: 85%
“…The validity of the outcomes determined by automated health record review has previously been compared with manual record review and patientreported outcomes. 36 Similar to another report, 37 this previous study 36 found large positive likelihood ratios with moderate sensitivity. Another study 38 Funding/Support: The study was supported by the Big Ideas Program, a BJC HealthCare and Washington University School of Medicine internal grant program hosted by the Healthcare Innovation Lab and the Institute for Informatics (Dr Abraham).…”
Section: Limitationssupporting
confidence: 85%
“…SATISFY-SOS tracks intermediate-term postoperative outcomes; patients complete postoperative surveys (approximately 1 month and 1 year after surgery) that includes the Veterans Rand 12 Item Health Survey (VR-12), a validated measure of QoL. QoL will be a secondary outcome in this subset of patients; based on our prior work with SATISFY-SOS, 1500 to 2000 responses (versus ~1 00 000 extracted the EHR) will be available for analysis 38. We will not link to delirium or other assessments from independent studies conducted during this period at BJH (ENGAGES, PODCAST).…”
Section: Methodsmentioning
confidence: 99%
“…QoL will be a secondary outcome in this subset of patients; based on our prior work with SATISFY-SOS, 1500-2000 responses (versus ∼100,000 extracted the EHR) will be available for analysis. 38 We will not link to delirium or other assessments from independent studies conducted during this period at BJH (ENGAGES, PODCAST).…”
Section: Methodsmentioning
confidence: 99%